Kerapatan dan Tutupan Kanopi Mangrove di Perairan Sei Nyirih Pulau Bintan - Firmansyah, Dandy; Azizah, Diana; Susiana, Susiana (Universitas Jambi, 2025)
Sei Nyirih is a river located between Madong Village and Sei Nyirih Village. The area has a mangrove ecosystem that is utilized by the government as a mangrove educational tourism area and utilized by the local community as a fishing area. This study aims to determine the density level of mangrove species and determine the mangrove canopy cover in the Sei Nyirih waters. This research was conducted in March-April 2024. The method used was a direct survey method in the field. By using random sampling, 15 points were randomly taken spread across the Sei Nyirih Waters. Each point has one research plot. There are six types of mangroves found at 15 research points, namely: Rhizopora apiculata, Rhizopora mucronata, Bruguiera gymnorrhiza, Bruguiera sexangula, Ceriops tagal, Xylocarpus granatum. The types of mangroves Rhizopora apiculata, Rhizopora mucronata, and Xylocarpus granatum are the types that are always found at each sampling point. From 15 research points, the canopy cover % value ranged between 56.7% - 85.2%. Based on KEPMENLH No.201 of 2004, it is included in the Good and Very Dense categories. The lowest mangrove canopy cover was found at point six which is a mangrove tree felling. The highest mangrove canopy cover was found at point one which is a point whose location is far from population activities.